New metropolitan perspectives knowledge dynamics, innovation-driven policies towards the territories' attractiveness. Volume 1 - Bevilacqua, Carmelina, 1965-; Calabrò ed Anzalone, Francesco, 1776-1859; Spina, Lucia Della
This open access book presents the outcomes of the symposium "NEW METROPOLITAN PERSPECTIVES," held at Mediterranea University, Reggio Calabria, Italy on May 26-28, 2020. Addressing the challenge of Knowledge Dynamics and Innovation-driven Policies Towards Urban and Regional Transition, the book presents a multi-disciplinary debate on the new frontiers of strategic and spatial planning, economic programs and decision support tools in connection with urban-rural area networks and metropolitan centers. The respective papers focus on six major tracks: Innovation dynamics, smart cities and ICT; Urban regeneration, community-led practices and PPP; Local development, inland and urban areas in territorial cohesion strategies; Mobility, accessibility and infrastructures; Heritage